2011
DOI: 10.1128/jvi.02211-10
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Foamy Virus Protease Activity by Viral RNA: a Novel and Unique Mechanism among Retroviruses

Abstract: Foamy viruses (FVs) synthesize the Pol precursor protein from a specific transcript. Thus, in contrast to what was found for orthoretroviruses, e.g., human immunodeficiency virus, no Gag-Pol precursor protein is synthesized. Foamy viral Pol consists of a protease (PR) domain, a reverse transcriptase domain, and an integrase domain and is processed into a mature protease-reverse transcriptase (PR-RT) fusion protein and the integrase. Protease activity has to be strictly regulated in order to avoid premature Gag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 38 publications
2
56
0
Order By: Relevance
“…In contrast to the human immunodeficiency virus type 1 (HIV-1) RT heterodimer (p66/ p51), prototype FV (PFV) PR-RT has been shown to be monomeric and able to catalyze all RT-related functions (3), while PR activation requires dimer formation of the PR domain via the binding of PR-RT to a specific element on the viral RNA, called the protease-activating RNA motif (PARM) (4,5). Hence, for the retrotranscription functions, PFV PR-RT differs from alpharetroviral and lentiviral RTs (including HIV-1 RT), which are dimeric, and it is similar to the gammaretroviral RTs that are monomeric (6).…”
mentioning
confidence: 99%
“…In contrast to the human immunodeficiency virus type 1 (HIV-1) RT heterodimer (p66/ p51), prototype FV (PFV) PR-RT has been shown to be monomeric and able to catalyze all RT-related functions (3), while PR activation requires dimer formation of the PR domain via the binding of PR-RT to a specific element on the viral RNA, called the protease-activating RNA motif (PARM) (4,5). Hence, for the retrotranscription functions, PFV PR-RT differs from alpharetroviral and lentiviral RTs (including HIV-1 RT), which are dimeric, and it is similar to the gammaretroviral RTs that are monomeric (6).…”
mentioning
confidence: 99%
“…Whereas Lee et al (19) reported a role of the IN domain within the precursor protein for inducing PR dimerization and enzymatic activity, Hartl and colleagues (18) described the stimulation of PFV PR activity by a PFV vRNA element, the protease-activating RNA motif (PARM). PFV PR dimerization by PARM involves two purine-rich sequences and seems to be mediated by RNA binding to the RT domain with no need for the IN domain (18,20).…”
mentioning
confidence: 99%
“…However, mature PFV p85 PR-RT was shown to be monomeric in solution and to lack proteolytic activity under physiologically relevant conditions in vitro (17). The mechanism of PR activation is a controversial subject (18,19). Whereas Lee et al (19) reported a role of the IN domain within the precursor protein for inducing PR dimerization and enzymatic activity, Hartl and colleagues (18) described the stimulation of PFV PR activity by a PFV vRNA element, the protease-activating RNA motif (PARM).…”
mentioning
confidence: 99%
“…We propose that by this mechanism cDNA synthesis is delayed until sufficient amounts of Gag and Pol are cleaved to ensure viral infectivity. This checkpoint is needed, because cDNA synthesis leads to degradation of the protease-activating RNA motif (PARM), which is essential for protease activity in FV (8) and therefore terminates processing of Gag and Pol.…”
mentioning
confidence: 99%
“…First, we exchanged the wildtype Gag cleavage site sequence RAVN-TVTQ with residues GAL G-ALGA in the context of the codon-optimized expression plasmid ( Fig. 1) (8,9). This plasmid was named p71⌬CS (Fig.…”
mentioning
confidence: 99%